2017
DOI: 10.1002/dneu.22473
|View full text |Cite
|
Sign up to set email alerts
|

Retinal axon guidance at the midline: Chiasmatic misrouting and consequences

Abstract: The visual representation of the outside world relies on the appropriate connectivity between the eyes and the brain. Retinal ganglion cells are the sole neurons that send an axon from the retina to the brain, and thus the guidance decisions of retinal axons en route to their targets in the brain shape the neural circuitry that forms the basis of vision. Here, we focus on the choice made by retinal axons to cross or avoid the midline at the optic chiasm. This decision allows each brain hemisphere to receive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 131 publications
1
34
0
Order By: Relevance
“…However, this may not be the case as the genetic determinants and nature of 102 retinocortical miswiring differ in achiasma, FHONDA, and albinism (Hoffmann and Dumoulin, 103 2015;Ahmadi et al, 2018). Moreover, albinism itself is a heterogeneous syndrome with a wide 104 variety of genetic and phenotypic subtypes (Oetting et al, 1994; Simeonov et al, 2013; 105 Montoliu et al, 2014; Wilk et al, 2014b;Prieur and Rebsam, 2017). In a previous study 106 (Woertz et al, 2019), we describe significant variation in the pattern of hemifield eccentricity 107 representations in subjects with albinism with retinotopy that ranges from nearly normal to 108 highly aberrant, thus suggesting that pRF properties in albinism might also vary considerably.…”
mentioning
confidence: 99%
“…However, this may not be the case as the genetic determinants and nature of 102 retinocortical miswiring differ in achiasma, FHONDA, and albinism (Hoffmann and Dumoulin, 103 2015;Ahmadi et al, 2018). Moreover, albinism itself is a heterogeneous syndrome with a wide 104 variety of genetic and phenotypic subtypes (Oetting et al, 1994; Simeonov et al, 2013; 105 Montoliu et al, 2014; Wilk et al, 2014b;Prieur and Rebsam, 2017). In a previous study 106 (Woertz et al, 2019), we describe significant variation in the pattern of hemifield eccentricity 107 representations in subjects with albinism with retinotopy that ranges from nearly normal to 108 highly aberrant, thus suggesting that pRF properties in albinism might also vary considerably.…”
mentioning
confidence: 99%
“…Additionally, albinism is associated with an abnormally increased chiasmal decussation of the nerve fibres originating from the temporal hemi-retinae (Guillery, Okoro, & Witkop, 1975). Axon guidance at the chiasm is regulated by a number of molecular mechanisms at the retina (Prieur & Rebsam, 2016).…”
mentioning
confidence: 99%
“…Since our original demonstration that the RPE plays a key role in early development of the mammalian neural retina 32 , a considerable amount of work has been performed, including in the albino Tyr−/− mouse, that sheds light on the primary cause for visual deficiency in OCA1 patients [for review see 33 ]. In particular it was shown that the lack of melanin and/or intermediates along the melanogenesis pathway leads to retinal developmental defects, especially in the neurogenesis of ganglion cells, and that defective guidance of their axons along the optic tracts results in optic chiasm misrouting and impairment of binocular vision [for review see 34 ]. Despite extensive investigation using partial rescue of tyrosinase activity in the Tyr−/− model 3538 , it is still not clear which factors in the pigment synthesis pathway are involved and if they directly signal from the RPE to the neural retina or if they primarily affect RPE integrity.…”
Section: Discussionmentioning
confidence: 99%